An Assessment of Women Empowerment Programmes in Rural Areas of Benue State - Agbo, Mary (2015)
The study examined and appraised the programmes and projects of government, non-governmental organizations (NGOs), Civil Society Organizations (CSOs) and international agencies in empowering women in the rural areas of Benue State. It also identified the various problems and prospects associated with the empowerment of the rural women, with a view to examining the trend of women empowerment and effectiveness of the policy and programmes in the rural areas of the state. Data were collected from both primary and secondary sources. Primary data were collected through questionnaire, in-depth interviews, participant observations, and focus group discussions (FGDs). The study area covered six rural local government areas (LGAs), namely, Katsina-Ala, Ushongo, Gwer, Guma, Oju and Ohimini which were purposively selected from the three senatorial zones in the state. A random sampling technique was used to select three wards from each of the six LGAs, making a total of 18 wards. A total of 720 respondents were randomly drawn from a target population of 7,200 through Lottery method. Another set of questionnaire was administered on leaders and outstanding members of CSOs, while top officials of government ministries, NGOs, and international agencies involved in the programmes were interviewed. Twelve FGDs were conducted in four villages - Okpiko, Oglewu, Mbagba and Ikov – which were purposively selected because these were the most rural communities in the study area. The data collected were analyzed using descriptive and inferential statistics. The ZY Index Table was utilized to analyze the FGDs.